Corrective countermeasure for track transition zones in railways: Adjustable fastener. (15th August 2018) - Wang, Haoyu; Markine, Valeri
Graphical abstract: Highlights: A corrective countermeasure can immediately mitigate transition zones' degradation. Field measurements to record the value of accumulated voiding in transition zones. Considering the nonlinear contact between the ballast and sleeper. Dynamic behaviour of transition zones with and without the adjustable fastener. Abstract: Transition zones in railway tracks are the locations with considerable variation in the vertical stiffness of supporting structures. Typically, they are located near engineering structures, such as bridges, culverts, tunnels and level crossings. In such locations, the variation of the vertical stiffness and the differential track settlement result in amplification of the dynamic forces acting on the track. This amplification contributes to the degradation process of ballast and subgrade, ultimately resulting in the increase of maintenance costs. The paper studies a corrective countermeasure that can mitigate the track degradation in transition zones when differential settlement appears. The countermeasure is the adjustable rail fastener and its working principle is to eliminate the gap under hanging sleepers by adjusting the shims (height of the fastener). The adjustable fasteners are first tested on three transition zones, wherein the adjusted heights of fasteners (accumulated voiding) are recorded after the 2-month and 5-month operation. The test results show the adjustable fasteners are effective to mitigate the track degradation in the transition zones. The effect of the adjustable fasteners on the dynamic behaviour of transition zones is analysed using the FE method. The results show that the adjustable fasteners are effective to reduce the amplification of wheel forces, achieve a better stress distribution in ballast, and decrease the normal stresses in rails in transition zones. Parametric studies are also performed to study the applicability of the adjustable fasteners.